ANALISIS KINERJA AUDITOR INTERNAL DALAM MENCEGAH TERJADINYA FRAUD KREDIT FIKTIF PT. BANK MUAMALAT CABANG MAKASSAR - Wawing, Andi; Khalid, Idham (Universitas Muhammadiyah Makassar, 2018)
This study aims to determine whether the performance of auditors in the Makassar Branch. The method of sampling technique used was purposive sampling, namely the technique of deliberate sampling. This study uses a simple linear regression analysis method and primary data manager using the SPSS program (Statistical Product and Service Solutions). Based on the results of the testing of the Partial Test (t-Test) the hypothesis is obtained that the Internal Auditor's Performance has a positive and significant influence on the Prevention of Fictional Credit Fraud. Testing the effect of Internal Auditor Performance variables on Fictional Prevention of Fraud can be seen by looking at the value of t count of 3.737 and t table of 2.045 with a significance value of 0.001. The value of t count is greater than t table and the significance value is below 0.05 which indicates a significant effect of the Internal Auditor Performance variable on the Prevention of Fictional Fraud. So that the auditor's performance can prevent fictional credit fraud.